AN OPTIMIZATION MODEL OF MOBILE CHARGING STATIONS TO CHARGE ELECTRIC VEHICLES - Agustina Hery Indrawati, Dwi
The rapid adoption of Electric Vehicles (EVs) presents a challenge in meeting growing charging demands, particularly as Fixed charging stations (FCS) face limitations such as high installation costs and capacity constraints. The EVs will have quite some waiting time when they arrive at the fully occupied FCS. Mobile charging stations (MCSs) are one of the innovative flexible solutions to augment FCS. MCS can alleviate EV drivers’ range anxiety by carrying batteries traveling to EVs for charging. However, a common issue is the challenge of charging in places with heavy traffic or limited space. This study develops an optimization model for MCS on Batam Island using Agent-Based Modelling and Simulation (ABMS). The optimization is made to place a minimum number of MCSs to minimize the operating costs and charging capacity. Simulation results suggest that deploying MCSs near existing high-traffic FCS can significantly reduce charging queues and improve service distribution, particularly in areas with limited or no FCS coverage.